Implementation monitoring of city development strategy - the case study of Pančevo - Mikavica, Mihailo; Čolić, Ratka (Arhitektura i urbanizam, 2017)
This paper is the result of the research project carried out as part of master’s study programme Integral Urbanism at Faculty of Architecture, University of Belgrade. The main focus of master’s thesis was ’’Instruments for Governing Integral Urban Development’’. In year 2016, polygon used to create a master projects was the territory of the City of Pančevo, a development framework was: ’’City Development Strategy of Pančevo for the Period 2014-2020’’. Considering issues and potential improvement opportunities of the city, after research and analysis, we have chosen the research theme ’’Implementation Monitoring of City Development Strategy – The Case Study of Pančevo’’. The paper outlines the broader framework of urban development management to understand the implementation of new management tools of urban development in local context of the City of Pančevo. The focus is on instruments that improve process of the monitoring of implementation of local development strategies - human resources, financing, institutionalization and participation. The results of this master project relate to the proposals for improving the monitoring of the implementation strategy, including the manner and structure of reporting, establishing a team to implement the strategy as a permanent body, linking funding strategy with the program budget of the city and improving public participation and transparency in decision-making in the process of implementing the strategy. Results are derived from the research presented in this paper, and listed for better overview and operationalization issues in a local context. The focus of this work is on understanding the capacity of institutionalization of the changes in the domain of urban development in the local context in Serbia.